The Effect of Temperature on Soft Contact Lens Diameter. Issue 5 (September 2016) - Young, Graeme; Potts, Matthew; Sulley, Anna
Abstract : Purpose: The diameters of soft contact lenses are conventionally measured at room temperature (RT), however, all soft lenses shrink when raised to eye temperature (ET). The purpose of this study was to evaluate RT to ET shrinkage in a representative sample of contemporary spherical soft contact lenses. Methods: Twenty-four reusable and daily disposable lens types (10 hydrogel and 14 silicone hydrogel) in three powers were measured for total diameter at RT (20°C±1°C) and ET (34°C±1°C). Lens diameter measurements were undertaken after equilibration in ISO saline in a temperature controlled lens analyzer (Optimec Ltd, Malvern, UK). Theoretical changes in base curve radii were also calculated. Results: All lens types reduced in diameter when raised to ET. The largest mean changes with silicone hydrogel and hydrogel lenses were with Avaria (Δ0.33 mm) and SofLens Daily Disposable (Δ0.69 mm), respectively. The smallest mean changes for silicone hydrogel and hydrogel lenses were with 1-DAY ACUVUE TruEye (Δ0.04 mm) and SofLens 38 (Δ0.11 mm), respectively. There was, however, a wide range in change between the different lenses tested. Conclusions: This study has identified the levels of shrinkage in current soft contact lenses. In many cases, these shrinkage levels can be expected to have significant effects on clinical performance.